2019
DOI: 10.1086/701425
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Depression in Adolescence

Abstract: The probability of being depressed increases dramatically during adolescence and is linked to a range of adverse outcomes. Many studies show a correlation between religiosity and mental health, yet the question remains whether the link is causal. The key issue is selection into religiosity. We exploit plausibly random variation in adolescents' peers to shift religiosity independently of individual-level unobservables that might affect depression, and show conditions such that an individual effect of religiosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 51 publications
2
32
1
Order By: Relevance
“…Overall the results are quite similar to those in Table 5. 27 As anticipated in the earlier results, the estimates on non-school expenditures get notably larger with trend controls, suggesting a 40 cents-on-the dollar effect. But the result consistently suggests a decline in non-school revenue when vouchers expand.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Overall the results are quite similar to those in Table 5. 27 As anticipated in the earlier results, the estimates on non-school expenditures get notably larger with trend controls, suggesting a 40 cents-on-the dollar effect. But the result consistently suggests a decline in non-school revenue when vouchers expand.…”
Section: Resultssupporting
confidence: 72%
“…Recent decades have seen a large rise in the fraction of Americans reporting no religious affiliation, and even giving to religious causes (traditionally largest area of charitable giving by far) has begun to fall while giving overall continues to grow (Hout and Fischer, 2002;Velasco, 2015;Campbell and Putnam, 2012;Voas and Chaves, 2016). This shift is noteworthy as studies have shown that religiosity is strongly related to a variety of economically and socially relevant outcomes (Fruehwirth, Iyer, and Zhang, 2016;Hungerman, 2014;Fletcher and Kumar, 2014; see Iyer, 2016 for a review), and that congregations provide a variety of public goods, often jointly with the government. 2 In this time of declining religion, our work suggests that such joint provision represents not only a source of competition between church and state but also a potentially crucial source of subsidization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Besides, in this paper, I also show how selection issues can be mitigated by carefully designing experiments in a natural setting. My study thus relate to the liter-5 Various studies have shown how religion/religiosity influences economic outcomes, such as contributions to public goods (Benjamin et al, 2016); educational outcomes (Oosterbeek & van der Klaauw, 2013); discrimination (Chuah et al, 2016); economic growth and happiness (Campante & Yanagizawa-Drott, 2015); trust and ethics (Guiso et al, 2003); charitable giving (Shariff & Norenzayan, 2007); competition with social groups Norenzayan et al (2016); views toward out-group members (Clingingsmith et al, 2009); and, mental health (Fruehwirth et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…For example, church attendees gain social capital by participating in shared community events and investing time with one another, building trust and social links that influence their economic decision making (Putnam and Campbell 2010). These social ties can play an important role in facilitating financial development and development of informal networks (Glaeser, Laibson, and Sacerdote 2002; Guiso, Sapienza, and Zingales 2004), which could help cushion against risk over the business cycle (Dehejia, DeLeire, and Erzo 2007). However, religious participation may also affect well‐being directly by altering the way individuals process and deal with information and circumstances.…”
Section: Introductionmentioning
confidence: 99%